The relationship between sosiodemographic factors and public knowledge of herbal medicines in two districts in Sleman Regency - Dian Medisa; Hady Anshory; Putri Litapriani; Rezky Fajriyati M (Jurnal Ilmiah Farmasi, 2020)
AbstractIntroduction: The use of herbal medicines in the community is increasing, both in developing and developed countries.. Most people use herbal medicine for generations or based on experience. Therefore, it is necessary to analyze the public knowledge about herbal medicine to support the use of herbal medicines appropriately and correctlyObjective : To determine the relationship between sociodemographic characteristic with public knowledge level about  herbal medicine in Sleman Regency.Methods: Survey research conducted on the people of Minggir and Cangkringan districts, Sleman Regency. Sampling of 240 respondents was done by cluster sampling method. Data obtained from the distribution of questionnaires that have been validated to the public. The correct answer was counted and scored, then responden who score greater or equal to the mean were grouped into good knowledge, whereas those who score less than mean were grouped into poor knowledge. Data were analyzed by univariate and bivariate by chi-square test.Result : The majority of respondents were women (61.2%) and the most age was 26-45 years (46.7%). The respondents' knowledge is the best in the domain of how to use herbal medicine with an average percentage of correct answers 67.6%. In the domain of side effects, the average percentage of answers is only 47.7%. Overall respondents who had a good level of knowledge were 66.2% and respondents who were poorly knowledgeable were 33.8%. The results of the bivariate analysis showed no correlation between sociodemographic characteristics and knowledge level about herbal medicine (p> 0.05).Conclusion: Most people in Sleman Regency have good knowledge about herbal medicine. However, education still needs to be done about herbal medicines, especially the efficacy and side effects. Keyword: knowledge, herbal medicine, sleman regencyIntisariLatar Belakang: Penggunaan obat herbal (OH) di masyarakat semakin meningkat, baik di negara berkembang maupun negara maju. Sebagian besar masyarakat menggunakan obat herbal secara turun temurun atau berdasarkan pengalaman. Oleh karena itu, perlu dilakukan analisis terhadap pengetahuan masyarakat tentang obat herbal untuk mendukung penggunaan obat herbal dengan tepat dan benar.Tujuan: Untuk mengetahui hubungan sosiodemografi dengan tingkat pengetahuan masyarakat tentang obat herbal pada dua kecamatan di Kabupaten Sleman.Metode: Penelitian survey yang dilakukan pada masyarakat Kecamatan Minggir dan Cangkringan, Kabupaten Sleman. Pengambilan sampel sebanyak 240 responden dilakukan dengan metode cluster sampling. Data diperoleh dari pembagian kuesioner yang telah tervalidasi. Responden yang memiliki skor di atas nilai rata-rata termasuk dalam kategori berpengetahuan baik, sedangkan jika dibawah atau sama dengan rata-rata termasuk kategori berpengetahuan buruk. Data dianalisis menggunakan uji chi-square.Hasil: Mayoritas responden adalah wanita (61,2%) dan usia paling banyak 26-45 tahun (46,7%). Persentase pengetahuan yang paling baik yaitu pada domain efek samping obat herbal (78,3%), sedangkan pengetahuan yang terendah tentang cara penggunaan obat herbal (32,1%). Lima puluh lima persen responden memiliki pengetahuan yang baik tentang obat herbal secara keseluruhan. Hasil analisis bivariat menunjukkan faktor sosiodemografi tidak berhubungan secara signifikan dengan tingkat pengetahuan responden tentang obat herbal (p<0,05).Kesimpulan: Faktor sosiodemografi tidak berhubungan dengan tingkat pengetahuan tentang obat herbal. Pengetahuan tentang obat herbal dapat ditingkatkan melalui pemberian edukasi yang sesuai dengan kebutuhan dan kondisi sosiodemografi masyarakat.Kata kunci: pengetahuan, obat tradisional, Kabupaten Sleman